Practicing Futures through Voicing : Choreography as Conditioning 2 - Andersen, Tawney; Langsdorf, Heike (Gent : Art Paper Editions, 2019)
Contributors: Tawny Andersen, Alex Arteaga, Gaia Carabillo, Boyzie Cekwana, Lauren Grusenmeyer, School of Love, Sébastien Hendrickx, Heike Langsdorf, Bauke Lievens, Barbara Raes
boek